Phylogenetic re-evaluation of the Grosmannia penicillata complex (Ascomycota, Ophiostomatales), with the description of five new species from China and USA. Issue 2 (February 2020) - Yin, Mingliang; Wingfield, Michael J.; Zhou, Xudong; de Beer, Z. Wilhelm
Abstract: The Grosmannia penicillata complex (Ophiostomatales, Ascomycota) is one of the major species complexes in Leptographium sensu lato . Most of these are wood staining fungi associated with conifer-infesting bark beetles, and the complex encompasses the type species of the genus Grosmannia . Yet the phylogenetic relationships of species within the complex is unresolved. The aim of this study was to re-evaluate the circumscriptions of all known species in the G. penicillata complex, as well as isolates resembling G. penicillata obtained from a recent survey in China. Phylogenetic analyses of four gene regions: Internal transcribed spacer 2 and large subunit (ITS2-LSU), beta-tubulin (TUB), calmodulin (CAL), and translation elongation factor 1 alpha (TEF-1α) resolved the relationships of 15 species, including four new species ( Grosmannia xianmiense sp nov., Grosmannia purpurea sp. nov., Grosmannia crassifolia sp. nov. and Grosmannia maixiuense sp. nov.), from China. Some isolates from pine in the USA that had previously been identified as Grosmannia abietina, represented a distinct taxon that is described here as Grosmannia xeno-abietina sp. nov. Highlights: Phylogenetic analyses of four gene regions (ITS2-LSU, β-tubulin, calmodulin, translation elongation factor 1-α) were used. Four new species from China and one new species from USA associated with conifer-infesting bark beetles were described. One lectotype was designated, and seven new combinations were provided.